Evaluation of cardiac enzymes in early diagnosis of heart disease (Eurasian Journal of Research, Development and Innovation, 2024)
This study was conducted to achieve the goal of early detection of some heart diseases, which are one of the leading causes of death in the world, using some indicators and their role in clinical diagnosis. The current study included 25 samples of sick people visiting the eye and safety laboratories for pathological analyzes and each of Ramadi Teaching Hospital, Fallujah Teaching Hospital, and Hit General Hospital. And Salah alDin General Hospital, with ages ranging between 26-85 years and for the period from 1/25/2021 to 5/27/2021. The study showed that there is an increase in the percentage of cardiac enzymes in people who smoke more than in people who are non-smokers, and there is a clear difference in the percentage between males and females